Career success: Constructing a multidimensional model - Dries, Nicky; Pepermans, Roland; Carlier, Olivier (Journal of vocational behavior, 2008)
A multidimensional model of career success was developed aiming to be more inclusive than existing models. In a first study, 22 managers were asked to tell the story of their careers. At the end of each interview, idiosyncratic career success “construct ladders” were constructed for each interviewee through an interactive process with the interviewer. The 42 superordinate career success operationalizations that came forward through this process were then used as input in a Q-sort study in which 30 subject matter experts (SMEXs) served as judges. Through multidimensional scaling (MDS), a model incorporating the different idiosyncratic meanings the interviewees attached to the career success construct was obtained. A two-dimensional configuration (affect–achievement versus intra-personal–inter-personal) comprising nine regions (performance, advancement, self-development, creativity, security, satisfaction, recognition, cooperation and contribution) was concluded upon as the optimal solution. Correspondences with earlier conceptual models of career success are spelled out.